The Relationship between Physical Activity and Quality of Life in Patients with Congestive Heart Failure (CHF) - Aliya Marsiana; Mohammad Arifin Noor; Suyanto Suyanto (Lembaga Pengembangan Kinerja Dosen, 2026)
Background: Maintaining long-term regular physical activity is crucial for several weeks. Unfortunately, only 10% of patients benefit from cardiac rehabilitation programs after hospitalization for acute heart failure, and the majority of patients do not pursue long-term physical activity. The purpose of this study was to determine the relationship between physical activity and quality of life in CHF patients at Sultan Agung Islamic Hospital, Semarang. Method: This study was a quantitative study using a cross-sectional design. Data collection was conducted using a questionnaire. A total of 108 respondents were selected using a purposive sampling technique. The data obtained were analyzed statistically using the chi-square test. Result: Based on the analysis, it was found that of the 108 respondents, the average age was 55 years, the average diagnosed with CHF for 3 years, with the characteristics of the majority of male gender, namely 66.7%, the last education was high school level as much as 56.6%, and the majority worked as private employees as much as 47.2%. The results also showed that 65.7% of respondents had moderate activity, 27.8% had light activity and 6.5% had heavy activity. A total of 61.1% of respondents had a good quality of life, 31.5% had a moderate quality of life, and 7.4% had a poor quality of life. Conclusion: There is a significant relationship between physical activity and quality of life (p-value <0.05).